Non-disclosure of violence among female sex workers: evidence from a large scale cross-sectional survey in India. - Bidhubhusan Mahapatra (Public Library of Science (PLoS), 2014)
Objective One of the indicators critical to the success of violence reduction programmes among female sex workers (FSWs) is the pattern of disclosure of violence. This study examines the rate of non-disclosure of violence among FSWs in India by perpetrators of violence and programme exposure. Methods Data were drawn from a cross-sectional study conducted among FSWs in 2009 across four states of India: Andhra Pradesh, Karnataka, Maharashtra and Tamil Nadu. The analytical sample included 1341 FSWs who experienced physical violence in past six months. Multilevel logistic regression stratified by state was conducted to examine predictors of non-disclosure. Results About 54% of FSWs did not disclose their experience of violence to anyone with considerable variations in the pattern of disclosure across states. Another 36% of FSWs shared the experience with NGO worker/peer. Compared to violence perpetrated by paying partners/stranger, that by non-paying partner were twice more likely to report non-disclosure (53% vs. 68%, Adjusted Odds Ratio [AOR]: 1.8, 95% Confidence Interval [CI]: 1.3-2.4). Similarly, FSWs who were not registered with an NGO/sex worker collective were 40% more likely to report non-disclosure of violence against those registered (58% vs. 53%, AOR: 1.4, 95% CI: 1.1-1.9). Conclusions Non-disclosure of physical violence is quite high among FSWs which can be a barrier to the success of violence reduction efforts. Immediate efforts are required to understand the reasons behind non-disclosure based on which interventions can be developed. Community collectivisation and designing gender-based interventions with the involvement of non-paying partners should be the way forward.